2009
DOI: 10.1007/s00431-009-0956-6
|View full text |Cite
|
Sign up to set email alerts
|

Off-label, off-limits? Parental awareness and attitudes towards off-label use in paediatrics

Abstract: Off-label drug use in paediatrics is associated with an increased risk of adverse drug reactions. Any risk–benefit analysis has to be based on value judgments that should include parents' views. However, nothing is known so far about the parents' perspective on this critical issue. Therefore, a quantitative survey with parents of healthy and chronically ill children was carried out (n = 94). Knowledge about the practise of off-label use is generally poor in both groups. Surprisingly, this is also true for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…The high prevalence of antibiotic prescriptions for off-label indications or at unregistered doses in our NICUs and pediatric wards is in line with previously published data concerning the pediatric use of antibiotics [1][2][3][4][5][6][7][8][9][10][11][12]. It may be that pediatricians have a poor understanding of the properties and characteristics of antibiotics nor how they should be prescribed to treat bacterial diseases at different pediatric ages, but our findings raise some interesting afterthoughts.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The high prevalence of antibiotic prescriptions for off-label indications or at unregistered doses in our NICUs and pediatric wards is in line with previously published data concerning the pediatric use of antibiotics [1][2][3][4][5][6][7][8][9][10][11][12]. It may be that pediatricians have a poor understanding of the properties and characteristics of antibiotics nor how they should be prescribed to treat bacterial diseases at different pediatric ages, but our findings raise some interesting afterthoughts.…”
Section: Discussionsupporting
confidence: 79%
“…Over the last few years, several studies carried out in different settings have clearly demonstrated that the off-label use of drugs is frequent in pediatrics, especially in neonates [1][2][3][4][5][6][7][8][9][10][11][12]. However, most of them have considered all drugs prescribed to children and provided little details of prescription practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the willingness of parents to consent for their children to take part in clinical trials is associated with the worsening of the child's health status and when children can directly benefit from the clinical research. [18,19] The present study showed that this also holds true for healthcare professionals who are themselves parents.…”
Section: Discussionsupporting
confidence: 62%
“…[18] In an earlier public opinion survey carried out in Northern Ireland, a significant percentage of parents/guardians reported that they would refuse the use of such medicines or ask for the prescription of a licensed alternative if they were informed about the unlicensed use of medicines in their child. In addition, the majority of participants in that latter study (92.1%) felt that parents should be told if their child was being prescribed a medicine that had not been fully studied or licensed in children.…”
Section: Discussionmentioning
confidence: 99%